Prevalence of Gastrointestinal Parasites of Goats in and around Jabalpur, Madhya Pradesh - Lata, Kusum; Das, G; Kumbhakar, Nitesh; Saiyam, Rupanjali (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted to investigate the prevalence of gastrointestinal (GI) parasites of goats in and around Jabalpur. During 9 months of study period, out of 1675 faecal sample of goats examined, 1224 (73.07%) were found positive for different gastrointestinal parasites. The maximum prevalence recorded was of Strongyles (61.43%) followed by Coccidia (25.97%), Amphistomes (9.73%), Monieziaexpansa (8.66%), Trichuris spp. (2.03%), Strongyloides spp. (1.79%) and Fasciolagigantica (0.66%). When prevalence was compared in goats maintained at field and farm conditions, significantly higher infection (P
Keywords: Gastrointestinal parasite; Goats; Prevalence; Jabalpur